Wonder and the Marvellous from Homer to the Hellenistic World - Lightfoot, Jessica (Humanities, 2021)
Shows that wonder and wonders constituted a central theme in Greek culture from Homer to the Hellenistic period. Argues for its importance in discussions of the purpose of philosophy and literature and in expressions of the relationships between the human and the divine and between self and other.